Metode Pembinaan Hukum terhadap Anak Belum Cakap Hukum di Lembaga Pembinaan Khusus Anak II Maros: Analisis Madhab Fikih - Pratiwi, Annisa Intan; Aisyah, Nur; Laman, Ilham (Universitas Islam Negeri Alauddin Makassar, 2024)
The main problem in this research is how the legal guidance process for children who are not yet legally competent is implemented at the Special Children's Development Institute II Maros and what is the impact of legal guidance on children who are not yet legally competent at the Special Children's Development Institution II Maros according to the school of jurisprudence. The research method used in this research is sociological legal research by conducting direct interviews. Meanwhile, this type of research is included in field research, namely research that has been carried out directly at the object, especially in an effort to collect data and various information by describing in detail the implementation of coaching at the II Maros Children's Special Development Institute. The research results obtained show that the concept of coaching methods applied by the Special Children's Development Institute II Maros is divided into three, including: Independence Development. Religious Development, and Skills Development. According to Imam Syafi'i, applying coaching methods to children who are not yet competent by providing education and teaching has a good impact so that children can understand and practice Islamic teachings. Meanwhile, according to Imam Maliki's opinion, the application of coaching methods to children who are not legally competent by providing advice and guidance has a good impact. The implication of the research is that when applying the coaching method to children who are not legally competent, they still provide coaching using the advice method, but it is done gently so that the child can easily accept it in accordance with the Imam Maliki school of thought and the coaching method for developing knowledge should be given learning in the form of providing basic material so that the children being coached receive educational simulations. the same as the level of education in public schools.